New features of agricultural legislation in the sphere of breeding and seed production - Kuzmich, Iryna P. (Journal of the Belarusian State University. Law, 2023)
The article defines the features of legal regulation of relations in the breeding and seed production field based on the analysis of regulatory legal acts of the Republic of Belarus, taking into account the impact of the agreed agro-industrial policy pursued on the territory of the Eurasian economic union. General and key development trends of legislation specific to the legal regimes of circulation in the seed market and breeding products are identified. The characteristic of the institutional environment is presented, providing interaction between the state, producers and consumers of seeds and breeding products.
Keywords: agrarian legislation; agrarian policy; state register; Eurasian Economic Union; animal husbandry; breeding business; breeding products; legal regime; agricultural plants; seeds; seed production